2008
DOI: 10.1071/fp07228
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of lactate dehydrogenase during hypoxic stress in Arabidopsis

Abstract: During waterlogging conditions plants switch from aerobic respiration to anaerobic fermentation to cope with the lack of available oxygen. Plants have two main fermentation pathways: ethanol and lactic acid fermentation. In this paper we carry out a functional analysis of the Arabidopsis lactate dehydrogenase gene, LDH1. Our results indicate that LDH1, like some other anaerobic genes, is expressed in a root-specific manner and is affected by a variety of abiotic stresses (hypoxia, drought, cold) and mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 32 publications
1
60
1
Order By: Relevance
“…The high activity of LDH (Figure 10), and consequently, the signaling mechanism is required to initiate or promote the activity of ADH in the stimulation of ethanolic fermentation, by consuming more protons than lactic, increasing the cytosolic pH survivability of plants subjected to waterlogged conditions (Dolferus et al, 2008), which explains the results obtained in this study.…”
Section: Conditionssupporting
confidence: 76%
“…The high activity of LDH (Figure 10), and consequently, the signaling mechanism is required to initiate or promote the activity of ADH in the stimulation of ethanolic fermentation, by consuming more protons than lactic, increasing the cytosolic pH survivability of plants subjected to waterlogged conditions (Dolferus et al, 2008), which explains the results obtained in this study.…”
Section: Conditionssupporting
confidence: 76%
“…Overexpression of PDC, considered to be rate limiting in ethanol fermentation, has been shown to increase Arabidopsis survival Ismond et al, 2003). Increased root survival was also observed in LACTATE DEHYDROGENASE (LDH)-overexpressing Arabidopsis lines (Dolferus et al, 2008). Altering the expression of ALANINE AMINO-TRANSFERASE, which controls the Ala fermentation pathway, did not affect tolerance to low oxygen in Arabidopsis Miyashita et al, 2007).…”
mentioning
confidence: 89%
“…Multiple signaling pathways are triggered transcriptionally in response to flooding (Klok et al, 2002;Fukao and Bailey-Serres, 2008;Hattori et al, 2009). Functional studies of plant flooding and the effects of low oxygen have mainly focused on altering the expression of the genes encoding the enzymes for fermentation and glycolysis (Ellis et al, 1999;KĂźrsteiner et al, 2003;Bieniawska et al, 2007;Dolferus et al, 2008). Transcriptomic studies have revealed that expression of huge numbers of genes (;10% genes assayed) is altered upon flooding (Klok et al, 2002;Liu et al, 2005;Kreuzwieser et al, 2009;van Dongen et al, 2009;Hsu et al, 2011), suggesting that global transcriptional regulatory networks play important roles in response to flooding.…”
Section: Introductionmentioning
confidence: 99%